Assessment of the Socrative platform as an interactive and didactic tool in the performance improvement of STEM university students - Roberto Gómez-Espina; Delia Rodríguez-Oroz; Manuel Chávez; Cristian Saavedra; María Jesús Bravo (Laureate Education Inc, 2019)
This paper collects and analyzes students' academic results related to the change in teaching methodologies used in different subjects of different science and engineering university courses between 2013 and 2016. This change means introducing active methodologies such as gamification and ICT instead of a traditional methodology. With this purpose the use of Socrative, a platform that has been designed for the educational field, was introduced during said period. Interaction with the Socrative platform took place in well prepared classrooms with computers and internet connections, including the use of personal mobile devices (laptops, smartphones and tablets) according to the BYOD methodology. The active methodology implemented allowed students to improve their academic results while learning and improving their passing rates.